Kepemimpinan Silmy Karim: Mendorong PNBP melalui Kebijakan dan Kepemimpinan Swasta Pada Birokrasi Imigrasi Dalam Perspektif Bela Negara - Rasona Sunara Akbar; Ferdyan Samuel Karunia; Dimasyati Nusa Al-Fath; M Irvan; Antang Williem; M Dhafin Fadhilah; Fakhri Muammar; Arianda Rizki Ryantama (Departement of Mathematics Education, 2024)
Effective leadership in the context of immigration management is an important element in achieving the country's goals of optimizing Non-Tax State Revenue (PNBP) and increasing progress in the immigration sector. This study explores the leadership role of Silmy Karim, a private figure who has responsibilities in the Directorate General of Immigration, by focusing on the influence of integrity and the spirit of defending the country in his leadership. The concept of learning by doing and the corporate management approach are also the focus in analyzing the strategies and principles applied by Silmy Karim. Through a qualitative approach, data was collected through interviews, observations and study of related documents. The research results show that Silmy Karim's leadership significantly influenced the increase in PNBP and progress in immigration management. Integrating the values of integrity and the spirit of defending the country in the performance of the Directorate General of Immigration is the key to achieving significant results. The implications of private leadership in the management of government agencies are also highlighted in the closing.